2020
DOI: 10.1016/j.urology.2019.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR Based Urinary Tract Infection (UTI) Analysis Compared to Traditional Urine Culture in Identifying Significant Pathogens in Symptomatic Patients

Abstract: To evaluate whether multiplex PCR-based molecular testing is noninferior to urine culture for detection of bacterial infections in symptomatic patients. METHODS Retrospective record review of 582 consecutive elderly patients presenting with symptoms of lower urinary tract infection (UTI) was conducted. All patients had traditional urine cultures and PCR molecular testing run in parallel. RESULTS A total of 582 patients (mean age 77; range 60-95) with symptoms of lower UTI had both urine cultures and diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 27 publications
6
64
1
7
Order By: Relevance
“…The introduction of multiplex PCR testing, which utilizes multiple primers to detect several targets at once has dramatically reduced the cost and time associated with this class of test as well as increasing its utility in clinical medicine [32]. It is particularly useful for identifying infectious agents, and has been studied for several types of infections including but not limited to bloodstream infections, sexually transmitted infections, and gastrointestinal infections [33]. The appeal of PCR-based diagnostic testing for UTI's lies in its high specificity and sensitivity as well as the rapidity with which results can be obtained compared to standard bacterial cultures for the previously named infections [34][35][36], among others.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of multiplex PCR testing, which utilizes multiple primers to detect several targets at once has dramatically reduced the cost and time associated with this class of test as well as increasing its utility in clinical medicine [32]. It is particularly useful for identifying infectious agents, and has been studied for several types of infections including but not limited to bloodstream infections, sexually transmitted infections, and gastrointestinal infections [33]. The appeal of PCR-based diagnostic testing for UTI's lies in its high specificity and sensitivity as well as the rapidity with which results can be obtained compared to standard bacterial cultures for the previously named infections [34][35][36], among others.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…The appeal of PCR-based diagnostic testing for UTI's lies in its high specificity and sensitivity as well as the rapidity with which results can be obtained compared to standard bacterial cultures for the previously named infections [34][35][36], among others. PCR not only has higher detection rates of single pathogens compared to urine culture [37][38][39], but has been shown to be effective in detecting multiple pathogens in urine, which standard urine cultures routinely fail to do [33]. This is of great importance considering that between 30-39% of UTI's are polymicrobial [33,[40][41][42] and appropriate antimicrobial treatment is dependent on accurate identification of the causative organisms.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to significant maternal colonization or infection, and subsequent fetal transmission, a growing body of evidence supports pre-natal diagnosis (preferably by a NAAT methodology) and treatment of these microbes [32] [33] We found that detection of polymicrobial infections (3 or more pathogens) in the urine samples of the pregnant population was significantly higher than the overall detection rate ( Figure 4). A recent study of symptomatic UTI patients demonstrated that multiplex PCR was able to detect the presence of pathogenic agents in 36% of concurrent, parallel "split samples", that tested negative with traditional culture techniques [34]. In addition, the same study detected polymicrobial infections in 12% of culture negative samples.…”
Section: Resultsmentioning
confidence: 94%
“…10 Multiplex PCR based tests for UTI can improve the detection rate of uropathogens when widely available. 11 Identification of UTI pathogens should trigger a referral pathway to urology services for further evaluation of prostate and urinary tract pathology.…”
Section: Discussionmentioning
confidence: 99%